2015
DOI: 10.1007/s10103-015-1856-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of micropulse transscleral cyclophotocoagulation in advanced glaucoma

Abstract: Glaucoma is the leading cause of irreversible blindness worldwide. The goal of this study was to describe our experience with the novel micropulse transscleral cyclophotocoagulation (MP-TSCPC; IRIDEX IQ810 Laser Systems, CA) in patients with advanced glaucoma. Patients with advanced glaucoma who underwent MP-TSCPC were included in our study. Laser settings were 2000 mW of 810 nm infrared diode laser set on micropulse delivery mode. The laser was delivered over 360° for 100-240 s. The duty cycle was 31.3 %, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
129
4
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 14 publications
10
129
4
6
Order By: Relevance
“…Our experience with MP-TSCPC showed a 33.12% reduction in IOP at last follow-up, a rate that is similar to other published reports on MP-TSCPC [ 15 ]. There were no cases of hypotony, phthisis bulbi, or ocular prolonged inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Our experience with MP-TSCPC showed a 33.12% reduction in IOP at last follow-up, a rate that is similar to other published reports on MP-TSCPC [ 15 ]. There were no cases of hypotony, phthisis bulbi, or ocular prolonged inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Early studies of MP-TSCPC suggest success rates over 70%, but long-term results are not available for this novel procedure. 24,25 In our survey, surgeons indicated that they used CPC of any method most frequently for eyes with prior SB, neovascular glaucoma, and prior PKP. Future surveys can assess whether the availability of ECP and MP-TSCPC will shift the use of CPC toward more low-risk eyes.…”
Section: Discussionmentioning
confidence: 89%
“…MicroPulse™ transscleral cyclophotocoagulation (MP‐TSCPC) offers a safe and effective alternative to traditional TSCPC in humans . With this system, the laser beam is “chopped” into a train of repeated short, microsecond, “on” pulses followed by longer‐duration “off” intervals.…”
Section: Introductionmentioning
confidence: 99%